Study on Main Factors Contributing to Organizational Effectiveness: A Classification of Factors Influencing Organizational Effectiveness (Journal of Advances and Scholarly Researches in Allied Education, 2011)
There are manyways to measure success, a number of factors consistently show up ineffectiveness metrics. It is also important for a manager to identify theunderlying factors in organizational effectiveness. Individually, each factor matters in affecting organizationaleffectiveness. But, the more important is each factor’s relationship to theentire organization. Singh and Chhabra (2000) classified the factorsinfluencing organizational effectiveness into following three groups: